Growth, Governance, and Fiscal Policy Transmission Channels in Low-Income Countries - Kojo, Naoko (IMF Working Papers; Working Paper ;, 2003)
Private investment is the principal transmission channel through which fiscal policy affects growth in high-income countries. In low-income countries, governance and also other considerations suggest that the primary channel is factor productivity. Empirical results reported in this paper confirm this expectation: in low-income countries, factor productivity is some four times more effective than investment as a channel for increasing growth through fiscal policy. Although the private investment response to fiscal contraction may be minor, high-deficit, low-income countries can nonetheless benefit from a reduction in unsustainable fiscal deficits because of governance-related factor productivity responses that increase growth.